2016
DOI: 10.1007/s00425-016-2552-0
|View full text |Cite
|
Sign up to set email alerts
|

Vitamins for enhancing plant resistance

Abstract: This paper provides an overview on vitamins with inducing activities in plants, the molecular and cellular mechanisms implicated, and the hormonal signalling-network regulating this process. Moreover, it reports how vitamins might be part of the molecular events linked to induced resistance by the conventional elicitors. Induced resistance (IR), exploiting the plant innate-defense system is a sustainable strategy for plant disease control. In the last decade, vitamins have been proven to act as inducers of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 103 publications
3
55
0
1
Order By: Relevance
“…Vitamins have been reported as resistance inducers under conditions of biotic stress (Boubakri et al, 2016). In this context, studies on the use of vitamins such as thiamine have mainly focused on the management of pathogens (Boubakri et al, 2012(Boubakri et al, , 2016.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Vitamins have been reported as resistance inducers under conditions of biotic stress (Boubakri et al, 2016). In this context, studies on the use of vitamins such as thiamine have mainly focused on the management of pathogens (Boubakri et al, 2012(Boubakri et al, , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamins have been reported as resistance inducers under conditions of biotic stress (Boubakri et al, 2016). In this context, studies on the use of vitamins such as thiamine have mainly focused on the management of pathogens (Boubakri et al, 2012(Boubakri et al, , 2016. However, recent research has shown that thiamine treatments in barley crops reduce aphid population by 60% compared with untreated plants (Hamada and Jonsson, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Konsentrasi yang digunakan, untuk vitamin B ialah : a. 30 mM (Boubakri et al, 2016), b. koloidal kitin 1 g l -1 (Suganda, 2001), c. asam salisilat 5% (Sarwar et al, 2011), d. K2HPO4 13,6 g l -1 (Sarwar et al, 2011), dan e. Bion M 1/48 1,5 g l -1 (Sarwar et al, 2011).…”
Section: Pendahuluanunclassified